Volkswagen : steering a crisis - Comiteau, Lauren, (SAGE business cases, 2017)
In September 2015, what has become the world's largest automotive scandal began to unfold as US regulators charged Volkswagen (VW) with using software in some of its diesel engines that could fool emissions tests into thinking the affected vehicles were within permissible US pollution limits. What followed has been two years of investigations, admissions, lawsuits, penalties and disclosures that have affected not only VW but the entire automotive industry. VW has been in crisis management mode ever since, seeing a scandal that it initially blamed on a few rogue engineers reach into the top echelons of its corporate structure and resulting in billions of dollars of fines. How one of the world's most respected and largest automakers handled the events that even a top executive called an "existence-threatening crisis" is the topic of this case study in crisis management, written to include events up until March 2017.